Daytime, Not Nighttime, Elevated Atmospheric Carbon Dioxide Exposure Improves Plant Growth and Leaf Quality of Mulberry (Morus alba L.) Seedlings - Shi, Songmei; Qiu, Yuling; Wen, Miao; Xu, Xiao; Dong, Xingshui; Xu, Chenyang; He, Xinhua (Frontiers in Plant Science, 2021)
Almost all elevated atmospheric CO2 concentrations (eCO2) studies have not addressed potential responses of plant growth to different CO2 in daytime and nighttime. The present study was to determine the impact of daytime and/or nighttime eCO2 on growth and quality of mulberry (Morus alba L.) trees, a perennial multipurpose plant. Six-month-old mulberry seedlings were hence grown in environment auto-controlled growth chambers under four CO2 concentrations: (1) ambient CO2 (ACO2, 410 µmol mol-1 daytime/460 µmol mol-1 nighttime), (2) sole daytime elevated CO2 (DeCO2, 710 µmol mol-1/460 µmol mol-1), (3) sole nighttime elevated CO2 (NeCO2, 410 µmol mol-1/760 µmol mol-1), and (4) continuous daytime/nighttime elevated CO2 (D+NeCO2, 710 µmol mol-1/760 µmol mol-1). Plant growth characteristics, nutrient uptake and leaf quality were then examined after 120 days of CO2 exposure. Compared to control, DeCO2 and (D+N)eCO2 increased plant biomass production and thus the harvest of nutrients and accumulation of leaf carbohydrates (starch, soluble sugar, fatty acid) and N-containing compounds (free amino acid and protein), though there were some decreases in the concentration of leaf N, P, Mg, Fe and Zn. NeCO2 had no significant effect on yield but to an extent positive effect on nutritional quality on leaf. Meanwhile, (D+N)eCO2 decreased mulberry leaf yield and harvest of nutritious compounds for silkworm when compared to DeCO2. The reason may be associated to N, P, Mg, Fe and Zn that are closely related to leaf pigment and N metabolism. Therefore, the rational application of mineral nutrients (especially N, P, Fe, Mg and Zn) fertilizers is important for sustainable production of mulberry tree under future atmosphere CO2 concentrations.